Analisis Efisiensi Penggunaan Modal Kerja Untuk Meningkatkan Profitabilitas Di KSP Kopdit Pintu Air Cabang Kewapante - Maria Silvia Hape; Yosefina Andia Dekrita; Elisabet Luju (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
This research was carried out to determine the efficiency of the use of working capital to increase profitability at Pintu Air Credit Union of Kewapante Branch. The population in this research were the financial statements of Pintu Air Credit Union of Kewapante Branch, while the sample of this study were the financial statements of Pintu Air Credit Union of Kewapante Branch in 2017 to 2021. In collecting data, documentation and interviews were two techniques used by the researcher. The data analysis teachnique used were the liquidity ratio with the calculation of the current ratio, the activity ratio with the calculation of working capital turnover, and the profitability ratio with the calculation of Return on Assets (ROA). The results of data analysis from the assessment of each ratio showed that the liquidity ratio using the calculation of the current ratio of Pintu Air Credit Union of Kewapante Branch in the 2017 and 2018 periods decreased with the standard measurement of the efficiency of the use of working capital, which was in good criteria. In 2019 to 2021 the results had increased with the standard of efficient use of working capital categorized as very good. The activity ratio using the calculation of working capital turnover had decreasd and was considered poor in the standard of measuring the efficiency of using working capital with poor criteria. The profitability ratio using ROA obtained fluctuating results from 2017 to 2021 and on average was said to be quite efficient in the standard of measuring the efficiency of using working capital.